﻿La rose de Notre-Dame de Noyon et sa place dans la technique et le décor du troisième chantier de la cathédrale - Hardy, Chantal (RACAR : Revue d'art canadienne / Canadian Art Review, 1986)
The rose-window has been very important in the development of fenestrage major elements in Gothic architecture. The earliest examples appear in the middle of the twelfth century on the Île-de-France and are not well-known, particularly those with free-standing colonnettes, a type which Viollet-le-Duc does not include in what is still the basic work of reference for the rose-window. There is a very old window of this type preserved in the cathedral of Noyon. A careful study reveals the importance of the form within the third campaign of the cathedral, ca. 1170-1185. After establishing its authenticity and general date, a detailed analysis places the window within the building, from the point of view of both technique and decoration. Three types of circular window were constructed during the course of this campaign. The rose-window of the Treasury shows the same type of insertion under the vault as the small polylobed oculus at the lower side, north of the nave (1170). The tracery of the rose-window is made of stone slabs cut into cusped voussoirs and of colonnettes en délit, both elements found from the beginning to the end of the campaign. The Treasury rose-window has a rare feature: a primitive method for securing the frame. The armature is fastened to the interior surface of the curved wedges leaving the colonnettes of the tracery free. This system seems to explain the presence of bilobed arches at the border of the frame, an innovation for the rose-window with colonnettes. The decoration of the rose-window is linked to the secondary decoration of the portal of the annex of the north arm of the transept, under the rose-window, as well as to the very ornate high part of the choir. The execution of the rose-window can be dated between these points, ca. 1170-1175. The archivolt of the rose-window includes the mascaron, a very important motif in the decoration of the cathedral of Noyon and also associated with the earliest rose-windows (Saint-Denis, ca. 1140). The workshop of Noyon is an important center in the development of Gothic architecture, particularly for the treatment of its windows grouped by pairs in the double walls system of the transept or composed with an oculus over twin lancets in the Bishop’s chapel. This last formula is recognized as the most direct source for the composition of the high windows of the nave of Chartres cathedral. However at Chartres the rose-window hollows out the entire wall beneath the formeret or the vault, often considered an original creation of the Master of Chartres. This type of piercing, however, was also used in the workshop of Noyon for the rose-window of the Treasury. The study of that rose-window accentuates, through this fact, the importance of the workshop in the development of the large elaborate gothic window.